Mango ginger (curcuma amada) inhibits collagen-induced arthritis by modulating inflammatory cytokine levels in rats - Karatas, Ahmet; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Ozercan, Ibrahim Hanifi; Koca, Suleyman Serdar; Şahin, Kazım (Tubitak Scientific & Technological Research Council Turkey, 2020)
Background/aim: Mango ginger (MG: curcuma amada) has antioxidant and antiinflammatory activities. The aim was to evaluate the antiarthritic potential efficacy of MG on collagen-induced arthritis. Materials and methods: Twenty-one female Wistar-albino rats were divided into three groups. Arthritis was induced by intradermal injections of type II collagen and Freund's adjuvant. MG extract was orally administered starting from the first collagen injection. TNF-alpha, IL-6, IL-17, obestatin, sclerostin, and DKK-1 serum levels were determined, and perisynovial inflammation and cartilage-bone destruction in the paws were histologically evaluated. Moreover, joint tissue TNF-alpha, IL-17, NF-kappa B, and COX-2 levels were analyzed. Results: TNF-alpha, IL-17, IL-6, and DKK-1 serum levels were increased, and obestatin and sclerostin serum levels were decreased in the arthritis group compared to the control group. However, MG supplements decreased TNF-alpha, IL-17, IL-6, and DKK-1 serum levels and increased obestatin and sclerostin serum levels. Similarly, while collagen injection increased tissue TNF-alpha, IL-17, NF-kappa B, and COX2 levels, MG decreased TNF-alpha, IL-17, and NF-kappa B levels. Moreover, MG ameliorated perisynovial inflammation and cartilage-bone destruction in the paws. Conclusion: MG ameliorates arthritis via actions on inflammatory ways and wingless (Wnt) signaling pathway. These results suggest that MG may have a considerable potential efficacy for the treatment of rheumatoid arthritis.
Keywords: Mango ginger; inflammation; collagen-induced arthritis; rheumatoid arthritis